2017
DOI: 10.1088/2053-1583/aa868f
|View full text |Cite
|
Sign up to set email alerts
|

Atomic mechanism for the growth of wafer-scale single-crystal graphene: theoretical perspective and scanning tunneling microscopy investigations

Abstract: Chemical vapor deposition (CVD) is the most promising approach for producing low-cost, highquality, and large area graphene. Revealing the graphene growth mechanism at the atomic-scale is of great importance for realizing single crystal graphene (SCG) over wafer scale. Density functional theoretical (DFT) calculations are playing an increasingly important role in revealing the structure of the most stable carbon species, understanding the evolution processes, and disclosing the active sites. Scanning tunneling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 201 publications
(223 reference statements)
1
13
0
Order By: Relevance
“…Since the advent of graphene, two-dimensional (2D) materials have been extensively explored due to their outstanding mechanical and electronic properties that hold great promise for device applications. In particular, for 2D elemental structures, such as borophene, silicene, germanene, and stanene, both theoretical and experimental studies have revealed the critical role of substrate in the epitaxial growth, as they usually require a metallic substrate as catalyst with appropriate lattice match, except for a few cases of van der Waals epitaxy on inert substrates. , Unfortunately, the strong interfacial interaction between substrate and the grown structure results in difficulty in transferring of the structure onto a device-ready surface, which restricts practical applications. An attractive yet challenging way is to synthesize 2D materials directly on a nonmetallic substrate, such as semiconductors or insulators. As a recent example, via a delicately designed precursor with a C–F motif at the right position, Kolmer et al rationally fabricated nanographene and nanoribbons on a rutile TiO 2 (001) . However, the design and synthesis of these molecular precursors are daunting challenges. In this sense, molecular beam epitaxy (MBE) on an appropriate substrate has the benefit of sole usage of their bulk crystalline counterparts as precursors, such as graphite rods, silicon and germanium wafers, tin, boron rods, phosphorus (P) crystals, and antimony and bismuth granules. , During the past decade, MBE has also become one of the most popular approaches for large-scale synthesis of 2D materials.…”
mentioning
confidence: 99%
“…Since the advent of graphene, two-dimensional (2D) materials have been extensively explored due to their outstanding mechanical and electronic properties that hold great promise for device applications. In particular, for 2D elemental structures, such as borophene, silicene, germanene, and stanene, both theoretical and experimental studies have revealed the critical role of substrate in the epitaxial growth, as they usually require a metallic substrate as catalyst with appropriate lattice match, except for a few cases of van der Waals epitaxy on inert substrates. , Unfortunately, the strong interfacial interaction between substrate and the grown structure results in difficulty in transferring of the structure onto a device-ready surface, which restricts practical applications. An attractive yet challenging way is to synthesize 2D materials directly on a nonmetallic substrate, such as semiconductors or insulators. As a recent example, via a delicately designed precursor with a C–F motif at the right position, Kolmer et al rationally fabricated nanographene and nanoribbons on a rutile TiO 2 (001) . However, the design and synthesis of these molecular precursors are daunting challenges. In this sense, molecular beam epitaxy (MBE) on an appropriate substrate has the benefit of sole usage of their bulk crystalline counterparts as precursors, such as graphite rods, silicon and germanium wafers, tin, boron rods, phosphorus (P) crystals, and antimony and bismuth granules. , During the past decade, MBE has also become one of the most popular approaches for large-scale synthesis of 2D materials.…”
mentioning
confidence: 99%
“…High‐throughput calculations can also provide valuable information for selecting the suitable experimentally known 3D compounds that can be exfoliated into 2D materials . Furthermore, multiple surface science characterization techniques, e. g. combined STM, XPS, Ultraviolet photoelectron spectroscopy (UPS), low‐energy electron microscopy (LEEM) and device evaluation are required to establish a complete picture of the growth mechanism, morphology and electronic properties …”
Section: Discussionmentioning
confidence: 99%
“…Precision synthesis of GNRs appears as a major challenge. To this end, on-surface synthesis based on the polymerization and planarization of tailor-made molecular precursors on metal surfaces under ultrahigh vacuum (UHV) conditions appears particularly powerful and offers the additional advantage of in-situ monitoring by atomic-resolution scanning probe microscopy [5][6][7][8][9][10]. Since the initial demonstration of 7-atomwide armchair-type GNRs (7-AGNRs) on a Au(111) surface using 10,10'-dibromo-9,9'-bianthryl (DBBA) as a precursor [11], a range of GNRs with different structures have been prepared via on-surface synthesis, such as armchair GNRs (N-AGNRs) with different widths N (N = 5, 6, 8, 9, 10, 13, 15 and 17) [12][13][14][15][16][17][18][19], zigzag GNRs (ZGNRs) [20], chevron-type GNRs [11,21], chiral (3,1)-GNRs containing zigzag and armchair edges [22], and heteroatom-doped GNRs with boron, nitrogen, oxygen, or sulfur [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%